Preparation of two kinds of immunocastration vaccines and their immune effects on male goats - Fuqiang Pan; Yumeng Guo; Panpan Cheng; Wei Qian; Mengdi Han; Qing Yi; Huihui Xie; Meng Cao; Yanqiuhong Li; Yuke Jia; Jiankun Cui; Xinbao Gong; et al. (Animal Bioscience)
Objective Post-pubertal male goats exhibit undesirable behaviors (fighting, mounting) and reduced growth due to high testosterone, while traditional castration causes stress. Immunocastration offers a humane alternative. This study aimed to develop effective immunocastration vaccines. Methods The gonadotropin-releasing hormone (GnRH) octamer vaccine (G8), luteinizing hormone receptor (LHR) and GnRH octamer tandem vaccine (LG) were developed and synthesized for this study. Forty 3-month-old male goats were randomly divided into four groups, and subjected to different treatments: surgical castration (SC group), immunization with the G8 vaccine (G8 group), immunization with the LG vaccine (LG group), or left intact (non-castration [NC] group). After the first immunization, serum antibodies and testosterone levels, as well as body weight, body size, and scrotal size, were measured at various time points. Testicular size and slaughter rate were measured at the time of slaughter, 20 weeks after the first immunization. Results Both vaccines effectively elicited the corresponding antibodies in male goats; the testosterone levels in the G8 and LG groups were significantly reduced compared to the NC group (p<0.01). Four weeks after the first immunization, this trend persisted throughout the experiment; the testicular organ index and size of the G8 group were significantly (p<0.05) smaller than those of NC group at slaughter. In comparison to the NC group, the seminiferous tubule diameter in the G8 and LG groups was significantly reduced (p<0.01), accompanied by a notable decrease in Leydig Cells and various stages of spermatogenic cells. Additionally, the weight gain of goats in the SC group was significantly lower than that of other groups two weeks after the first immunization (p<0.05). Conclusion The two immunocastration vaccines developed in this study effectively inhibit the testicular development and spermatogenesis in male goats, leading to a reduction in testosterone levels.